The Factors Influencing Waqifs’ Loyalty to Cash Waqf: A Preliminary Analysis - Intan Fatimah Anwar; Syadiyah Abdul Shukor; Nur Qamarina Sharom; Atika Atan; Yuslina Yusoff (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA